Challenges, Coping Strategies, and Resilience in Implementing the Matatag Curriculum: Insights from Elementary Teachers - Wabingga, Reyin Joy; Tomakin, Juvy Love (Journal of Interdisciplinary Perspectives, 2024)
This study aimed to explore the challenges, resilience, and coping strategies of elementary educators during the implementation of the MATATAG curriculum. Three teachers from particular Digos City elementary schools participated in the study. This study used a qualitative, phenomenological research approach and was carried out from August to November of 2024. Focus groups and in-depth interviews were used as data collection methods to generate responses. The challenges for elementary teachers in implementing the MATATAG curriculum are resource and material constraints, increased curriculum demands, and the need for enhanced professional development and support. Themes found on the impact of challenges on the resilience of elementary teachers in implementing the new curriculum are mental and emotional stress, doubts about one's ability to cope, and professional identity. Thus, Coping strategies were used with peer and team support, self-motivation, a positive outlook, and professional growth and adjustment. Authorities were advised to invest in supplying the required tools and materials, create professional development plans, and assist educators by creating a creative and encouraging work atmosphere.